Utilization of Several Agricultural Wastes into Briquette as Renewable Energy Source - Dani Widjaya; Almansyah Nur Sinatrya; Wahyu Kusumandaru; Ahmad Jupriyanto; Randy Trinity Nijkamp (PLANTA TROPIKA, 2022)
Tobacco stems contain 56.10% cellulose content, 15.11% lignin, 22.44% hemicellulose, and 44.61% total organic carbon, which can be used as a source of energy or fuel. This study aimed to utilize tobacco stems in a briquette form as alternative energy. The materials used in this study were tobacco stem waste, rice husk, wood charcoal, and coconut shell. The treatments used in this study consisted of T1 (100% of tobacco stems), T2 (80% of tobacco stem + 20% of coconut shell), T3 (80% of tobacco stem + 20% rice husk), and T4 (33.33% of tobacco stems + 33.33% of rice husk + 33.33% coconut shell). The fastest combustion rate was found at T3, 0.12 gram/sec, while T1 and T2 had the same combustion rate. T4, a mixture of various materials, had no significant difference compared to T1, T2, and T3. The highest calorific value of tobacco stem briquettes was in T4 (4127 Kcal/kg), and the lowest was in T1 (2343 Kcal/kg). The combustion rate of these tobacco stem briquettes was longer than that of charcoal briquettes, whose average burning rate is 0.234 grams/second. Overall, this study provides an overview of the best combination to create briquettes from agricultural waste.